HUBUNGAN KUALITAS PELAYANAN JASA PENDIDIKAN DENGANKEPUASAN SANTRI PONDOK PESANTREN ALMANAAR BATUHAMPAR - Ali Mustopa Yakub Simbolon; Supratman Dzakir; Radtria Alkaf; Supriadi Supriadi; Bashori Bashori (UIN Imam Bonjol Padang, 2023)
This research was conducted with the aim of knowing the relationship between the quality of educational services and the satisfaction of students at Pondok Pesantren Al-Manaar Batuhampar. The research method is correlational with a quantitative approach. The number of samples in this study were 79 respondents using the Probability Sampling technique in the Simple Random Sampling method. Data analysis used Rank Spearman correlation with the help of the IBM SPSS 22 application. The results showed that the quality of educational services has a fairly good relationship with studentsatisfaction of 31.3% and has a positive relationship. The positive meaning shows that the better the quality of educational services (X), the higher the level of student satisfaction (Y). and conversely, the worse the quality of educational services (X), the worse the level of student satisfaction (Y).